Determinant Analysis of Open Unemployment Level in Banten Province, 2018 Using Panel Data Regression - Isdhani Nurrahmah; Roy Pratama Wijaya; Syifa Rahmawati Hakim; Yusuf Yahya; Rani Nooraeni (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
This study aims to analyse the relationship of crude school participation rate, the number of poor people, and the GDRP growth rate to the open unemployment rate in Banten. The analytical method used in this study is panel data regression with fixed effect model estimation which is processed using statistical software EViews 10. The data that are used in this study are secondary data from Badan Pusat Statistik (BPS), by taking annual data for each district in Banten province from 2011 until 2018. The results of this study indicate that the GDRP growth rate significantly affects the open unemployment rate, but the crude school participation rate and the number of poor people do not significantly affect the open unemployment rate in Banten.